Empirical relationship on vortex formation and heat transfer coefficient (HTC) using synthetic jet cooling / Nawal Radhiah Mohamad Nasir - Mohamad Nasir, Nawal Radhiah (2023)
The size and complexity of modern electronic gadgets have increased, making heat dissipation problems more challenging to resolve. The management of temperature currently in place is inefficient. Due to their small size and ineffective heat transfer, compact electronic gadgets with high power requirements and miniature electronic components are prone to overheating. The relationship between vortex formation and the heat transfer coefficient (HTC) value has not received much attention from previous researchers. Synthetic jet (SJ) consists of a periodically moving diaphragm and cavity with a nozzle has been used in this research. During the ejection phase, the cavity fluid is discharged from the opening forming vortex that move from cycle 1, cycle 2 and cycle 3. The CFD software used for simulation is ANSYS FLUENT to simulate the fluid characteristic. The numerical simulations approximate the air flow as three-dimensional, unsteady, turbulent and incompressible. The solver used is Semi-Implicit Method for Pressure-Linked Equations (S.I.M.P.L.E) algorithm meanwhile the turbulence model that has been used wasK-co SST. Experiment has been carried out to obtain temperature in order to validate the simulation data. Optimization using Taguchi method has been carried out and an equation has been generated to predict the temperature response. Nozzle diameter is the most significant parameter that contribute to the highest response followed by nozzle to heated surface distance and cavity depth. Small volume and small cavity are better because they resulted to higher velocity output thus increasing the convection process between the force air and the heated surface. Distance range of 50 mm is adequate for the vortex to have strength and coherence without been affecting by the reverse suction flow. The ability of the vortex formation to reach the heated surface is important to maximize the HTC value and the radius of vortex formation does not play huge role if the distance between the vortex formation and the heated plate is high. It can be concluded that in order to maximize the heat transfer process, the vortex formation needs to reach out as close as possible to the heater surface and the equation developed able to predict the temperature response within the range parameter used in this research.